Last night at the Viper Room : River Phoenix and the Hollywood he left behind - Edwards, Gavin, 1968- (It Books, an imprint of HarperCollins Publishers, 2013)
In Last Night at the Viper Room, acclaimed author and journalist Gavin Edwards vividly recounts the life and tragic death of acclaimed actor River Phoenix--a teen idol on the fast track to Hollywood royalty who died of a drug overdose in front of West Hollywood's storied club, the Viper Room, at the age of 23. Last Night at the Viper Room explores the young star's life, including his childhood in Venezuela growing up under the aegis of the cultish Children of God. Putting him at the center of a new generation of leading men emerging in the early 1990's--including Johnny Depp, Keanu Reeves, Brad Pitt, Nicolas Cage, and Leonardo DiCaprio--Gavin Edwards traces the Academy Award nominee's meteoric rise, couches him in an examination of the 1990s, and illuminates his lasting legacy on Hollywood and popular culture itself.